Application of the Human Opportunity Index in Evaluating the Effectiveness of the Administration Process and Its Implication on Service Quality in Healthcare Units - Malik Ibrahim, Mozart; Ifadhila; Syeh Assery; Henri Kusnadi, Iwan; Faizah, Ana (Jurnal Sistim Informasi dan Teknologi, 2024)
This research aims to determine the inequality of opportunities in the health sector. Researchers identified three primary sources of information in a database search to construct the organizational health index: the permanent continuous household survey, the quarterly provincial household survey, and the administrative records of the Department of Health Statistics system. The study employed a data matching mechanism to merge the two databases but discovered discrepancies in the live birth and death data, leading to a lack of confidence in the data's quality. The results show that the evolution of health opportunities in the last decade is generally positive, although there are still gaps in access to health insurance and health checks during pregnancy. The study found that the gap was primarily due to socioeconomic differences between individuals. An analysis of changes in the organizational health index in the health sector shows that sectoral policies play a significant role in improving access to health services. This increase in access was primarily achieved by the region's health policies, which ensured proportional increases for all individuals. However, there needs to be a greater focus on equal opportunities for access to health services to ensure that all individuals have equal access to quality health services.